(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article analyzes that active work is underway to create various concepts of "industrial," "post-industrial," "techno-tronal," "information" societies, that under the influence of the scientific and technological revolution, the "ordinary" agrarian society will be replaced by an industrially developed "industrial" society, and the further development of technocratic civilization will cause many problems.